Is Economic growth sensitive to oil consumption shocks in Turkey? - Sen, Sedef; Uzunoz, Meral (TAYLOR & FRANCIS INC, 2017)
This paper examines both the equilibrium relationship and the causality relationship between oil consumption and economic growth in a sample period spanning 1965-2013 in Turkey. For this purpose, an autoregressive distributed lag bounds testing approach was applied in order to determine the long-run relationship between variables, and an asymmetric causality test was used in an effort to classify the impact of shocks on the variables into positive and negative. The results of the bounds test and asymmetric causality test show that there is a long-run relationship between variables and that there is a unidirectional Granger causality running from negative economic growth shocks to negative oil consumption shocks, from positive economic growth shocks to negative oil consumption shocks, and from positive oil consumption shocks to positive economic growth shocks.
Keywords: Asymmetric causality; ARDL; economic growth; oil consumption; BOOTSTRAP PANEL CAUSALITY; STATISTICAL-INFERENCE; ENERGY-CONSUMPTION; COAL CONSUMPTION; TIME-SERIES; UNIT-ROOT; COUNTRIES; COINTEGRATION; CHINA; REGRESSION; Energy & Fuels